107 Ambitions for palliative and end of life care: findings from a mapping survey about the use of the national framework. (14th March 2023) - Borgstrom, Erica; Henry, Claire; St-Ledger, Una; Jordan, Joanne
Abstract : Introduction: The Ambitions for Palliative and End of Life Care: a national framework for local action (2015) and relaunched in 2021 for an additional five years. Developed through partnership, the Framework provides a vision for action focused on six ambitions underpinned by eight foundations. Methods: An online survey to map usages of the Framework comprised of closed and open questions. Survey questions sought information on: primary Ambition(s) guiding the work; how the Framework was understood to enable this work; and, perceived challenges to use of the Framework. Responses were accepted between 30th November 2021 and 31st January 2022 via the JISC online survey platform; only full responses were recorded minimising missing data. Data for closed questions were analysed for frequency. Answers to the question about policy context were coded by content to produce a quantitative overview. Other qualitative free-text comments were analysed to identify recurring themes. Results: A total of 45 examples were collected covering all geographical areas. Most examples came from hospice and/or specialist palliative care settings. Each person is seen as an individual (Ambition 1) was most frequently identified as a primary focus for services. Each community is prepared to help (Ambition 6) was least frequently identified as a primary focus for services. The Framework is most frequently being used to provide guiding principles and to support education and training. Survey respondents perceive the Ambitions Framework to be providing a shared language about what matters in palliative and end of life care. Conclusion: Our findings suggest that there is appetite for further education and knowledge exchange about the Framework and how people have used it. We identified current gaps in the implementation of the Framework and suggestions on how to use the Ambitions document. A full report is available (Borgstrom et al. 2022). 1 Reference: Borgstrom E, Jordan J, Henry C. (2022) Ambitions for Palliative and End of Life Care: Mapping Examples of Use in Practice. Milton Keynes: The Open University. http://oro.open.ac.uk/82928/